Triatoma sordida stål 1859 (hemiptera, reduviidae : triatominae) in palms of northeastern Argentina - Bar, María Esther; Wisnivesky Colli, Cristina (Ministério da Saúde. Instituto Oswaldo Cruz, 2001)
Several palms species provide an important habitat for triatomines and associate vertebrates in tropical America. The objective of this work is to identify the triatomine species living in the palms of rural areas in the Province of Corrientes, and to estimate the potential epidemiological risk they represent for the residents of nearby houses. The survey was carried out in a palm community in Colonia Laurel, Department San Roque, Province of Corrientes, Argentina. Samplings were performed in October, November and December 1998; January, February and March 1999; May and June 1999. Thirty palms: 27 (90%) Butia yatay (Mart.) Becc. and 3 Acrocomia aculeata (Jacq.) Lodd ex Mart. were dissected. Triatoma sordida Stål 1859 was found in 96.2% of B. yatay and in all the A. aculeata palms. A total of 272 live T. sordida was collected; 36 of them (13.2%) were found in bird nests in the frond and the remainder in other locations of the tree. The mean number of triatomines per palm was 9.6 (range 1-60, mode 2). T. sordida was collected during all the sampling months and all stages were present at all seasons. The highest population density was reached in spring and the lowest in autumn. Trypanosoma cruzi was detected in 38.5% in feces of 174 examined insects and identified as such, both by microscopical examination and PCR. This is the first finding of T. sordida populations in B. yatay, an endemic palm of South America distributed in southern Brazil, Uruguay and northeastern Argentina. The high infection prevalence found in this work suggests that T. sordida plays an essential role in the maintenance of the wild T. cruzi transmission cycle in northeastern Argentina.
Keywords: Triatoma sordida; Palms; Wild triatomines; Butia yatay; Argentina